Healthcare management strategy, communication, and development challenges and solutions in developing countries (Lexington Books, 2014)
Healthcare Management Strategy, Communication, and Development Challenges and Solutions in Developing Countries describes the ways in which health services, public health administration, and healthcare policies are managed in developing countries, and how intercultural, intergroup, and mass communication practices weaken development efforts in those countries. The book is suitable for undergraduate students, libraries, and companies involved with government issues, foreign services, public health, third world development, and i.